“Estudio e implementación de un sistema de comunicación para la tele-gestión de medidores eléctricos basado en PLT” - Carabalí Nazareno, John Paúl (2016)
This paper presents the design of an electronic system, which is capable of converting the optical pulses generated by an electric power meter, and into information, in order to be interpreted by the development platform that incorporates communication capabilities PLT . This card features the microprocessor CY8CPLC20 which allows communication by power lines. Once this information is obtained by the slave module is transmitted to the master module, the PC recepta this information via the serial port using the RS-232 protocol communication. The PC will have the ability to both manage the data, and to control the connectivity or the electrical grid transmitting an instruction from the master module to the slave, this command interacts with an electronic circuit which allows or not the user access to the power grid. The data obtained by the PC are displayed on a web page as consumption curves generated in real time. In this project the study presented limitations presented in a communication PLT. It allows software updates and hardware to implement future corporate level.